Los Apasionados de la Creación. (Les Forçats de l´Art.) - LORTET, Aurélien (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2010)
The existence of each human being is comparable to a grain of sand lost in the immensity of the ocean and even seems to dust themselves, gathered up the coast, the dunes and the storms of humanity. Each grain of sand is important, however small, is a universe in itself, travelling and polished, shaped by the time of the waves. There are plenty to choose. I will put my attention on only two of these grains of sand, proposing as a token gesture, a tribute to my parents, but not before accepting in advance the danger and traps that will challenge me to talk about my family.